2018
DOI: 10.1016/j.jtos.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

International publication trends in dry eye disease research: A bibliometric analysis

Abstract: Purpose: To perform a bibliometric analysis in the field of dry eye disease (DED) research to characterize the current international status of DED research and to identify the most effective actors (journals, countries, authors) involved in this field Methods: Scientometric methods were used to evaluate global scientific production and development trends in DED research using the Web of Science Core Collection Results:The growth of the literature related to DED averaged 12.18% over the last 10 years. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 27 publications
1
48
0
Order By: Relevance
“…To investigate the most common search topics among the selected publications, an author's keywords evaluation was performed. Keywords analysis provide a synthesis of a research topic (GARFIELD, 1990), and present important terms that were addressed by the authors (BOUDRY et al, 2018). The terms considered as keywords can be used to analyze the trends of a research area and to show the existing gaps (GUO et al, 2016).…”
Section: Abstract Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the most common search topics among the selected publications, an author's keywords evaluation was performed. Keywords analysis provide a synthesis of a research topic (GARFIELD, 1990), and present important terms that were addressed by the authors (BOUDRY et al, 2018). The terms considered as keywords can be used to analyze the trends of a research area and to show the existing gaps (GUO et al, 2016).…”
Section: Abstract Analysismentioning
confidence: 99%
“…Common-pool resources (CPR) are defined as a natural or artificial resources large enough to not exclude multiple users. They are systems that generate finite quantities of resource units, so that one person's At the first search, the selected terms were applied to the Topic field, which searches for publications through the title, abstract, keywords of the authors and Keywords Plus (BOUDRY et al, 2018). Keywords Plus augmented the title-word and author keyword indexing by supplying additional search terms extracted from the titles of article references on WoS (GARFIELD, 1990).…”
Section: Common-pool Resources (Cpr)mentioning
confidence: 99%
“…Choosing the right database to conduct a bibliometric study is an important step, as each literature database provides different features than others [2] . Previous studies have used bibliometric analysis to analyze different medical disciplines, as using it in ophthalmology [3] , urology [4] , and orthopedics [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Schargus et al reported the 100 most cited papers in dry eye and found that 55% of these studies were published from the USA (19). Boudry et al reported the international publication trends in dry eye disease research (20). These two studies had provided the evidence of publication trends and most important DED studies.…”
Section: Introductionmentioning
confidence: 99%